2010
DOI: 10.1007/s11307-010-0363-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Decrease of Proliferative PET Tracer 18FLT in Bone Marrow after Carbon Ion Therapy in Lung Cancer

Abstract: ¹⁸FLT revealed that BM function decreased by small dose such as <4.2-4.4 GyE/1 fraction of CIRT and is eradicated by >4.2-4.4 GyE/1 fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…This finding is consistent with previous findings for x-irradiation (7,22,23), although only a few studies using carbon ion radiotherapy have been reported (25,28,29). Charged particle irradiation has been associated with better treatment outcomes and less damage to normal tissue than x-irradiation.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous findings for x-irradiation (7,22,23), although only a few studies using carbon ion radiotherapy have been reported (25,28,29). Charged particle irradiation has been associated with better treatment outcomes and less damage to normal tissue than x-irradiation.…”
Section: Discussionsupporting
confidence: 92%
“…The study presented an augmented approach for eliciting a better understanding of the BM compartment by combining the glycolytic activity of 18F-FDG PET and proliferative activity of 18F-FLT PET, each being acquired within a week’s duration for the same patient. Other studies using 18F-FLT for imaging the BM compartment have focused on particular regions of interest rather than providing a measure of the total active BM in the human body ( 28 , 30 ). Also, the nature of the proposed technique renders it possible to extract and quantify the active BM within any bone in the body.…”
Section: Discussionmentioning
confidence: 99%
“…This study describes the physiologic uptake pattern of 18 FLT in a small cohort of healthy young cats and can be used as a baseline for future clinical application and interpretation of 18 FLT‐based imaging in this species. 18 FLT‐PET and 18 FLT‐PET/CT have already been used successfully in humans to diagnose, characterize, and manage a variety of neoplasms and hematopoietic disorders . Moreover, veterinary reports involving naturally occurring canine lymphoma, sarcoma, and bronchoalveolar carcinoma have demonstrated the utility of 18 FLT in detecting neoplastic lesions, evaluating therapeutic response, and recognizing disease recrudescence in dogs; the latter case report highlighting 18 FLT's usefulness as an adjunct to 18 FDG in the presumptive discrimination of inflammation from proliferative tumor .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in humans have demonstrated the utility of 18 FLT in the diagnosis, staging, measurement of therapeutic response, and prediction of outcome in a variety of malignancies . 18 FLT‐PET has also been used to characterize proliferative bone marrow in relation to therapeutic planning, response to insult, and hematologic disease . Underscoring the potential for translation of this tracer into veterinary applications, early preclinical studies included normal and diseased dogs and two reports within the veterinary literature document the successful use of 18 FLT in dogs to characterize neoplastic disease and assess therapeutic response .…”
Section: Introductionmentioning
confidence: 99%